Showcasing talents: UiTMCPP Open Mic Night 2022 / Nur Husna Serip Mohamad, Nur Ilianis Adnan & Noor Azli Affendy Lee - Serip Mohamad, Nur Husna (Academy of Language Studies, 2023)
The UiTMCPP Open Mic Night 2022 was a remarkable showcase of artistic talents, where 32 students from various academic levels were given the opportunity to share their skills. This event, organised by the English Language Club of UiTMCPP in collaboration with He & She Coffee, took place on three separate occasions – 10 November, 5 December, and 15 December 2022. To encourage participation, there were no participation fees for prediploma, diploma, and degree students. Additionally, presenters and the organising committee were treated to free He & She Coffee muffins and coffee during each session. The beauty of this event is that anyone could sign up and showcase their talents while being broadcasted live on the club's YouTube channel.